Thulium fiber laser in BPH surgery: Bench to bedside - a systematic review on behalf of YAU Urotechnology Working Group - Taratkin, Mark; Checcucci, Enrico; Androsov, Alexander; Azilgareeva, Camilla; Brill, Boris; Morozov, Andrey; Puliatti, Stefano; Belenchon, Ines Rivero; Kowalewski, Karl-Friedrich; Rodler, Severin; Rivas, Juan Gomez; Cacciamani, Giovanni E.; et al. (Frontiers in Urology, 2022)
Introduction. The Thulium fiber laser (TFL) is a new device that in contrast to the other solid-state YAG-based lasers takes a different approach to pulse formation allowing for two different modes: in the QCW (quasi-continuous wave) function, TFL is convenient for soft tissue surgery and in the SP (Superpulsed) mode it is highly effective in lithotripsy. Thus, unlike the other thulium lasers (Tm:YAG), TFL can be used in a wide range of surgical procedures. Materials and Methods. We conducted a systematic search in 3 databases: Medline, Scopus and Cochrane library. All original articles (both preclinical and clinical) on TFL application in soft tissue surgery were included in data analysis. Results. In terms of its cutting properties, QCW TFL is not inferior to the other thulium lasers, and in fact allows for decreased carbonization (due to lower heat production) compared to continuous lasers (e.g. Tm:YAG). It has been used successfully in endoscopic enucleation of the prostate (EEP) and in en bloc resection of bladder tumors (ERBT). The efficacy and safety of this laser is comparable to TURP and simple prostatectomy, but the recovery period is shorter and the learning curve is slightly superior to other endoscopic procedures. There are no significant differences between TFL and Ho:YAG in terms of efficacy and safety during EEP. Unfortunately, there are no clinical studies that analyse the efficacy and safety of SP TFL in EEP or ERBT. Conclusion. TFL is a safe and effective tool for BPH surgery. In terms of parameters, it is in no way inferior to Tm:YAG or Ho:YAG during EEP. However, TFL surpasses these lasers in terms of usability and serviceability. These advantages are likely to render it more popular over time.